Seven principles for good practice in midterm student feedback. Issue 4 (1st October 2020) - Taylor, Rebecca L.; Knorr, Kris; Ogrodnik, Michelle; Sinclair, Peter
ABSTRACT: Midterm student feedback is a common process in post-secondary institutions that can lead to enhanced teaching practices and thereby potentially to higher ratings of instructional skills in summative course evaluations. At McMaster University, midterm student feedback is called a 'Course Refinement' and includes consultation with educational developers. As part of a multiphase study investigating teachers' perceptions of the Course Refinement process and its impact, this analysis presents effective attributes of the process as an adaptation of Chickering and Gamson's well-known 'seven principles for good practice in undergraduate education', as our findings align with their work. To our knowledge, this marks the first educational development adaptation of the 'seven principles'.